A Study on the Role of Public Health in Reducing the Abuse of Ambulance Services - Yadgir A. M. D. I. Tanveer (Public Health, 2025)
BackgroundDemand for emergency medical services or ambulance response is situated within the context of other healthcare and social welfare services. Worldwide ambulance providers have a wide variety of services available, but many services are struggling to meet service demand. Inappropriate use of ambulance services is one of the biggest concerns globally. The burden of using the ambulance services includes transporting non-critical patients to the hospital. Misuse of the ambulance services is a serious problem that must be addressed and solved.ObjectiveThe purpose of this study is to evaluate the public perception of appropriate usage of ambulance services and determine the applicable role of public health to reduce the inappropriate use of an ambulance.MethodologyA cross-sectional study was conducted to collect data from the general public using an online survey. The survey contains 9 questions that evaluate the public awareness of appropriate ambulance use. Participants are people from the public within the age of 18 and above.Sample SizeA total of N=97 of participants’ responses were used to analyze the data. Inclusion CriteriaComplete surveys and answer data using the English language. Exclusion CriteriaUncompleted surveys, and answered with other languages.ResultsDuring the online survey, a total of n=97 participants enrolled voluntarily. The majority of the residents are aware of when to and whom to call in case of a medical emergency. N=35 (36%) of the participants believe that ambulance services are misused. ConclusionThe conducted study demonstrated that almost 36% of participants believed abuse of ambulance services, though there might be numerous reasons for calling ambulance unnecessary. Public health plays a vital role to reduce inappropriate ambulance calls when both ambulance services and public health are integrated into one system of care.